Risk Factor Analysis of Musculoskeletal Disorders (MSDS) in Woman Shellfish Peeler (Geloina Erosa) in Pantai Cermin District - Kadillah Suherry; Putra Apriadi Siregar; Syafran Arrazy (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Woman shellfish peelers (Geloina Erosa) are at risk of developing musculoskeletal disease (MSDS) because of their activities that involve lifting, moving heavy items, carrying weights on the head, bending, or looking up when carrying weights. The majority of women's jobs in Pantai Cermin sub-district are shellfish peelers (Geloina Erosa). This study aims to identify risk factors for musculoskeletal disease (MSDS) in female peelers of Kepah Mussels (Geloina Erosa). Using a cross-sectional study design and quantitative methodology, the population in this study was 45 and The sampling technique used a total sampling of 45 respondents. The data was then analyzed using a correlation test with the help of the SPSS program. The results showed that age, length of work, duration of work, weight, and work posture affect the risk of musculoskeletal disease (MSDs) in female shellfish peelers (Geloina Erosa) in Pantai Cermin District. But years of service are negatively affected This signifies that the longer a person works, the lower their likelihood of experiencing. One strategy to reduce the possibility of musculoskeletal disease complaints (MSDs) is to increase awareness of work posture, comply with occupational safety health regulations, stretch before starting work to reduce pain in parts of the body that experience musculoskeletal disorders, suggestions for improving sitting posture so that the legs are not bent and rest when the body experiences pain to reduce the risk of complaints. The goal is to prevent work fatigue and complaints of MSDs. Women who do kepah peeling work are also expected to routinely stretch, take adequate rest and to reduce soreness in the calves of female shellfish peelers (Geloina Erosa) in Pantai Cermin District It is recommended to use tables and chairs with parallel heights so as not to bend the legs too much and wrap when stripping shells (Geloina Erosa).Keywords: MSDS risk, Shellfish peeler (Geloina Erosa), Women, Work Posture